Valuing the local within the global: A discourse analysis of professional development in a U.S.-Kurdish transnational university partnership - Thomas Highley; Connie Theado (Journal of Global Education and Research, 2022)
In an effort to support higher education in developing countries, partnerships between U.S. and international universities have surged, raising questions concerning the social equity of such linkages. Using a New Literacy Studies approach to discourse analysis, online transcripts from one such university partnership were analyzed to determine how language was used to negotiate a more equitable partnership through the adaptation of the social context of professional development activities. Discourse analysis of three relevant linguistic markers in the data suggests that cultural perspectives on professional development influenced the language choices made by university partners, reshaping the power structure toward greater social equity, and aiding in the completion of joint professional development goals. Findings underscore the importance of drawing on local knowledges in planning for and conducting transnational university partnerships.